AN ANALYSIS OF STUDENTS' DIFFICULTIES IN READING COMPREHENSION AT SMPN 05 TANAH PINOH BARAT - Tia Malinda; Aunurrahman Aunurrahman; Sahrawi Sahrawi; Maliqul Hafis (IKIP PGRI Pontianak, 2022)
Quantitative descriptive research was conducted to determine the students' difficulties in reading comprehension and the factors of students' difficulties at SMPN 05 Tanah Pinoh Barat. The subjects of this study were seventh grade students of SMPN 05 Tanah Pinoh Barat. Son. Samples were selected using purposive sampling. The purpose of this study was to determine the difficulties of students in reading comprehension, and the factors of students' difficulties in class VII SMPN 05 Tanah Pinoh Barat. Researchers used quantitative descriptive methods. The subjects of this study were students of SMPN 05 Tanah Pinoh Barat. Samples were selected using purposive sampling. Data collection techniques in this study using measurement techniques and indirect communication. The instruments used are reading test and closed questionnaire. The researcher gave a test with 20 multiple choice questions. After getting the data from the reading test, the researcher analyzed the data by calculating the students' scores on the tests that had been given to each class. Then the researcher categorizes the students' scores on the test based on their ability level. To find out the students' difficulties, the researcher calculated the percentage of students' difficulties in five aspects of reading comprehension. Data from closed questionnaires were analyzed by calculating the percentage of answers from students. The test results showed that the seventh-grade students of SMPN 05 Tanah Pinoh Barat had difficulties in five aspects of reading comprehension. Namely, the main idea, supporting details, vocabulary, inference, and references. The most challenging aspects for students are vocabulary with a percentage of 58%, and references by 62%. The main idea with the percentage of student difficulty 38%, supporting details 38%, and inference 42%. The results of the questionnaire show that students' difficulty in reading comprehension is caused by 3 factors, namely: Lack of understanding of reading material, difficulty in using reading strategies, and the last is limited vocabulary knowledge. The conclusion of this study is that students fail to understand vocabulary and make conclusions. These two aspects are the most difficult aspects for students.Keywords: Students Difficulties, Reading Comprehension, Descriptive Quantitative Method